Design and manufacture of wax pattern making machines with drill chisels for layer deposition manufacturing processes - W, Fitri Atmono Agus (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2022)
Layer Deposition Manufacturing (LDM) is a new method in Rapid Prototyping. Layer Deposition Manufacturing is used for complex, hollow or complex production and object processes. The LDM process can be done manually, namely by creating a print cavity on Win. The goal to be achieved from this research is to make a pattern making machine with drill chisels to make molded cavities in wax in the Layer Deposition Manufacturing process. This research is based on existing literature as a theoretical basis. The stages carried out in this study began with designing a pattern making tool, searching for tool components and materials, making tools, assembling and testing the tool to determine machine performance. Tests were carried out using a drill chisel diameter of 2 mm and 3 mm and a wax thickness of 5 mm and 10 mm.